Stolen Gods and Stolen Blessings? The Narrative Significance of Rachel’s Theft in the Intertextual Mapping of the Jacob Cycle - Michael, Matthew (Journal for Semitics, 2019)
Rachel’s theft of her father’s teraphim has generated little interest in modern studies of the Jacob cycle. The reason for this particular lack of attention comes partly from the obscurity of Rachel’s theft, and the perceived insignificance of this theft in the mapping of the Jacob stories. However, this treatment of Rachel’s theft often ignores the web of subtle intertextual connections between Rachel’s theft and Jacob’s earlier deception of his father. Drawing on these intertextual links, the present article engages the literary clues within the two stories that directly suggest the placement of Rachel’s theft and deception of her father in the same character zone with the earlier story of Jacob’s deception of his father. Consequently, the study provides a fresh engagement with an obscure theft by Rachel, and underscores its overall narrative significance to the Jacob cycle.